2015
DOI: 10.1103/physrevlett.114.143903
|View full text |Cite
|
Sign up to set email alerts
|

Optical Rogue Waves in Integrable Turbulence

Abstract: We report optical fiber experiments allowing to investigate integrable turbulence in the focusing regime of the one dimensional nonlinear Schrödinger equation (1D-NLSE). Our experiments are very similar in their principle to water tank experiments with random initial conditions (see M. Onorato et al. Phys. Rev. E 70 067302 (2004)). Using an original optical sampling setup, we measure precisely the probability density function (PDF) of optical power of partially coherent waves rapidly fluctuating with time. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
222
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(231 citation statements)
references
References 51 publications
7
222
0
2
Order By: Relevance
“…It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33]. One of the universal mathematical models for the rogue wave description is the one-dimensional focusing Nonlinear Schrödinger (fNLS) equation,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33]. One of the universal mathematical models for the rogue wave description is the one-dimensional focusing Nonlinear Schrödinger (fNLS) equation,…”
Section: Introductionmentioning
confidence: 99%
“…Rogue waves are waves of unusually large amplitude Am, whose appearance statistics deviates from the Gaussian distribution by exhibiting "heavy tails" in the probability density function (see [37] and references therein). The conventional amplitude criterion for rogue waves is Am/As > 2, where As is the significant wave height defined in oceanography as the average wave height (trough to crest) of the highest third of waves (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With the input pulse well-fitted by a Gaussian profile, the parameter T 0 = ∆τ /1.665 [13]. Simulations were used to select the input power such that the fibre length corresponded to close to the first compression distance, and the pulse intensity profile was measured using a customdesigned optical sampling oscilloscope (see [26] and Supplementary Information). The results obtained in this case are displayed in Fig.…”
mentioning
confidence: 99%
“…Later, J.M. Soto-Crespo, N. Devine and N. Akhmediev have demonstrated that in the case of higher condensate disturbances, the tails of the probability density function of wave amplitudes increases [38] (see also the works [38][39][40] where the non-Gaussian statistics was observed for the development of strongly fluctuating initial conditions). They concluded that only initial perturbations of significant amplitude can contain spatially localized breathers, that is consistent with the theory suggested here (the minimal amplitude of SLCP generated by breathers is determined by the perturbation width, see the second paragraph).…”
Section: Discussionmentioning
confidence: 99%